Postural Tremor Is Associated with Gait and Balance Impairments in Community‐Dwelling Older People. Issue 4 (19th February 2019) - Xu, Xitong; Chen, Jie; Chen, Meijie; Gu, Zhuqin; Ji, Shaozhen; Liu, Shuying; Chan, Piu
Abstract : Objectives: We sought to assess associations of postural tremor with gait and balance impairments among community‐dwelling older people in both cross‐sectional and longitudinal analyses. Design: A prospective cohort study. Setting: Communities in Beijing, China. Participants: This study included 7075 individuals aged 55 years or older. Measurements: Postural tremor was assessed using a two‐step method (tremor screening followed by a confirmation examination of positive cases) at baseline. Gait and balance performances were measured with the Tinetti Mobility Test at baseline and 1 year later. Results: At baseline, 45 (24.7%) of 182 tremor cases vs 663 (9.6%) of 6893 controls had gait and balance impairments. At 1‐year follow‐up, 19 (21.1%) of 90 tremor cases vs 416 (9.8%) of 4262 controls experienced a rapid decline in gait and balance performance. After controlling for potential confounders, postural tremor was associated with gait and balance impairments at baseline (odds ratio [OR] = 1.77; 95% confidence interval [CI] = 1.20‐2.62; p = .004) and a rapid decline in gait and balance performance at 1‐year follow‐up (OR = 1.99; 95% CI = 1.17‐3.39; p = .01). Conclusion: In this population‐based cohort study, we found postural tremor was associated with gait and balance impairments among community‐dwelling older people in both cross‐sectional and longitudinal analyses. Our findings suggest that motor function should be routinely evaluated and monitored in older people with postural tremor. J Am Geriatr Soc 67:799–803, 2019.